Is Performance-Based Budgeting Only a Mirage? - Firmansyah, Rizky (EQUITY, 2021)
The aim of this paper is to describe reality of performance-based budgeting in Indonesia. Bureaucratic reform still becomes important issue in the government area, especially in developing countries, including Indonesia. One part in bureaucratic reform is the change in government budgeting system. In many countries, this case seems to be imposed, thus the implementation is inappropriate to its truly concept. Critical theories become paradigm used in this paper. Critical theory of Habermas selected as methodology in achieving goal towards the writing of this paper, because Habermas’s thought is very suitable to the issue raised in this paper, which is consensus path that replaces revolution path as offered by Marx. The importance of interaction emphasized on Habermas’s thought becomes basic of analysis due to the interaction or communication based on norm, inter-subjective, demanding role internalization, demanding maintenance of social institution, and action in order to achieve understanding. Performance-based budgeting that should become solution in achieving people welfare still not optimally implemented yet. Physically, the resulted budget has been in performance-based budgeting; however, in fact, indicators of budgeting benefit to the fulfillment of public service still ignored. The incremental system, planning that not based on performance, budget inefficiency to the useless expenditure for public, high political interference, also less budgeting control keep involved in regional budgeting in Indonesia. Contradiction between politics and budgeting culture that implemented recently is obstacle for maximal implementation of performance-based budgeting system. This is the reason why the implementation of performance-based budgeting system in developing countries, including Indonesia, cannot be the same with developed countries. There are many research opportunities that can be followed up from this paper such as study about budgeting culture using ethnography perspective and in-depth research about philosophical aspect from performance-based budgeting ideology with state ideology.